THE EFFECTS OF OLIVE LEAF EXTRACT OINTMENT ON PAIN INTENSITY AND EARLY MATERNAL COMPLICATIONS IN PRIMIPAROUS WOMEN - Kaviani, Maasumeh; Sepasi, Sara; Azima, Sara; Emamghoreishi, Masoumeh; Asadi, Nasrin; Haghpanah, Sezaneh (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: This study aimed to assess the impact of olive leaf extract ointment on pain intensity and early maternal complications in primiparous women. Methods: This randomized clinical trial was conducted on 90 primiparous women. The participants were randomly divided into three groups each containing 30 women. Groups A, B, and C used olive leaf extract ointment, placebo ointment, and betadine solution at the episiotomy area three times a day for 10 d. Improvement of the episiotomy wound was evaluated using REEDA scale, and pain intensity were assessed through Visual Analogue Scale (VAS). The evaluations were performed 4 h and 3, 7, 10, and 14 d after delivery. Results: The results showed a significant difference between the olive leaf extract ointment group and the other groups regarding the improvement of episiotomy wound (p<0.001). Pain intensity also significantly was reduced in this groups 10 d after delivery (p=0.029). Conclusion: Olive leaf extract ointment was relatively effective in reduction of pain intensity and early maternal complications resulting from an episiotomy.